Politics as activity : praxis, poiēsis, and gesture in the work of Giorgio Agamben - Sjöblom, Katarina (Routledge, 2025)
Engaging with a fundamental question at the heart of the Western tradition of political thought, namely the question of political action, this book considers a broad range of issues, from resistance to political mobilization. It explores the nature of political activity by engaging with Giorgio Agamben and his key interlocutors such as Hannah Arendt and Alexandre Kojève. It offers new insights into the complexity of Agamben's political thought and intervenes in contemporary debates on issues such as identity politics and protest movements.A fresh contribution to Agamben scholarship and a rigorous reflection on one of the core political questions of the occidental tradition, this volume will be of interest to scholars and students from a broad range of subject areas, including political theory, political philosophy, political science, aesthetics, philosophy of language, and biopolitics.
Keywords: Agamben, Giorgio, -- 1942-; Political science -- Philosophy.; Act (Philosophy); Agent (Philosophy); Ontology.; Giorgio Agamben; Hannah Arendt; Alexandre Kojève; Political Action; elektronické knihy; electronic books